International mobility of the highly skilled, endogenous R&D, and public infrastructure investment - Volker Grossmann; David Stadelmann (Institute for the Study of Labor (IZA), 2008)
This paper theoretically and empirically analyzes the interaction of emigration of highly skilled labor, an economy's income gap to potential host economies of expatriates, and optimal public infrastructure investment. In a model with endogenous education and R&D investment decisions we show that international integration of the market for skilled labor aggravates between-country income inequality by harming those which are source economies to begin with while benefiting host economies. When brain drain increases in source economies, public infrastructure investment is optimally adjusted downward, whereas host economies increase it. Evidence from 77 countries well supports our theoretical hypotheses.
Keywords: F22; 330; Brain drain; cross-country evidence; educational choice; public infrastructure investment; R&D investment; Brain Drain; Infrastrukturinvestition; Forschung; Bildungsinvestition; Endogener technischer Fortschritt; Entwicklungskonvergenz; Welt